The influence of tone at the top management level and internal audit quality on the effectiveness of risk management practices in the financial services sector - Frank Kabuye (Taylor & Francis Group, 2019)
The purpose of this study is to examine the contribution made by the tone at the top management level and internal audit quality on the effectiveness of risk management practices (RMPs) in the financial services sector. This study is cross-sectional and correlational, and it uses firm-level data that were collected by means of a questionnaire survey from a sample of 62 financial services firms in Uganda. Results suggest that the tone at the top management level and internal audit quality are both significant predictors of effective RMPs. However, the predictive potential of tone at the top management level towards effective RMPs reduces when internal audit quality is present. These results support the idea that in terms of agency theory, top management should oversee and review the organization’s risks as a way of spearheading effective RMPs. Similarly, internal auditors should sufficiently and appropriately review and coordinate risk management efforts in the organization, since high-quality internal audits lead to effective RMPs. Top managers of financial services firms should encourage periodic reviews of the appropriateness and effectiveness of risk management systems and controls. At the same time, regulators should ensure that top managers of financial services firms have adequate risk management expertise, with no conflict of interest and apply mechanisms that detect significant risks in time. The study contributes to the strategic risk management position by showing that the tone at the top management level and internal audit quality sets pace for an organization culture towards effective RMPs.